(untitled) (Scientific journal of the Fergana State University, 2025)
The paper presents the results of many years of research by the authors in the mountainous and foothill zones of the south of Fergana. It has been established that there is a relatively high content of humus in humus-accumulative horizons of mountain-brown, carbonate soils in the south of Fergana, and active processes of humification and mineralization have been revealed both in natural conditions and under the influence of an anthropogenic factor. The profile distribution of humus enerji, carbon of organic substances and humic, as well as fulvic acids is typical for these soils of the region.